2020
DOI: 10.1515/ijfe-2019-0378
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heating effect on total phenolics and antioxidant activity of green and mature coconut water

Abstract: Coconut water (Cocos nucifera L.) from fruits of two ripening stages (green and mature) was used to perform microwave heat treatments. Three different heating conditions with maximum temperatures of 70, 80 and 90 °C were tested in three holding times (0, 2 and 4 min). The Total Phenolic Content (TPC) using the Folin-Ciocalteu method and ABTS radical scavenging capacity were evaluated for each combination of coconut fruit age, heating temperature and holding time. It was observed that green coconut water exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The TPC of coconut water is an essential property used to determine the quality of processed coconut water. Previous literature has reported that processing of coconut water in thermal techniques impacts TPC and antioxidant activity in coconut water (Arzeta‐Ríos et al, 2020; Mahdavi et al, 2011). This work records the TPC and antioxidant activity (AAO) of lyophilized coconut water.…”
Section: Resultsmentioning
confidence: 99%
“…The TPC of coconut water is an essential property used to determine the quality of processed coconut water. Previous literature has reported that processing of coconut water in thermal techniques impacts TPC and antioxidant activity in coconut water (Arzeta‐Ríos et al, 2020; Mahdavi et al, 2011). This work records the TPC and antioxidant activity (AAO) of lyophilized coconut water.…”
Section: Resultsmentioning
confidence: 99%